Research on the stability analysis of GNSS reference stations network by time series analysis - Gulal, Engin; Erdogan, Hediye; Tiryakioglu, Ibrahim (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2013)
Global Navigation Satellite System (GNSS) is being widely used for various purposes throughout the world. In recent years, Continuously Operating Reference Station (CORS) networks consisting of multiple GNSS systems have been set up and operating in many developed countries. In Turkey, CORS-TR has been operating since 2009. The aim of CORS-TR is fast, correct, and reliable collection of all kinds of geographic data, thus, speeding up the activities of cadastre, assuring organized urbanization, constituting the spatial infrastructure for relevant works of e-government, and monitoring plate tectonics. Therefore, in this article, we investigated 788 days of spatial behaviors of 20 CORS-TR stations located in the southwest of Turkey. GNSS observations recorded from stations were evaluated and time series analyses were conducted to reveal station behaviors. As a result of trend component analyses of time series it was determined that with the exception of a single station (KAMN), other stations were moving in the southwest direction (21.7 mm/year). This finding is in consistency with the region's tectonic plate movements. In the periodical component analyses, stations' daily, monthly, seasonal, annual and even biennial movements resulting from atmospheric and hydrologic loading, climatic and other effects were revealed. Additionally, statistically random white noise was determined in GNSS station positions due to sunspot changes and earth's irregular rotation around its own axis. Nevertheless, colored noise in correlation with time was also determined by scholastic component analyses. As a result of the analyses, AKHR station east movement component was defined by AR(2) model and the movements of other stations were defined by ARMA(p, q) type models of different models. The results regarding the movements of CORS-TR stations in this region and the causes for these results were in consistency with the movements and causes of GNSS stations in the region and throughout the world. These results indicate that stations of CORS-TR network located in Southwestern Anatolia were rather stable and able to be providing reliable, accurate and continuous data for national and international studies to be conducted in many fields. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Southwestern Anatolia; CORS-TR; GNSS time series; Monitoring tectonic plate; Power spectrum; Noise; POSITIONING SYSTEM MEASUREMENTS; MARMARA SEA REGION; CRUSTAL DEFORMATION; SOUTHERN CALIFORNIA; GPS; DISPLACEMENTS; ANATOLIA; VELOCITY; RATES; Engineering